Pengaruh PAD dan DAU terhadap Belanja Modal di Kabupaten Kuala Kapuas - Dieky Fahreza Putra; Saipudin Saipudin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
Researchers used multiple linear regression analysis methods, with 2 independent variables namely PAD, and DAU, using the dependent variable Capital Expenditures. The hypotheses proposed in this study are (1) PAD and DAU partially have a significant effect on capital expenditure, and (2) PAD and DAU have a significant effect on capital expenditure. This study indicates: (1) PAD has a significant effect in the level of 0.10 and has a positive impact on Capital Expenditure in Kuala Kapuas Regency during 2005-2017. (2) DAU variable has an insignificant effect but positively impacts Capital Expenditure in Kuala Kapuas Regency. (3) PAD and DAU jointly or simultaneously have a significant effect on capital expenditure.